UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAN EKSTRAK AIR KELOPAK BUNGA ROSELLA (HIBISCUS SABDARIFFA L.) TERHADAP BAKTERI STREPTOCOCCUS PNEUMONIAE - Komala, Oom; Rosyanti, Reni; Muztabadihardja, Muztabadihardja (BERITA BIOLOGI, 2013)
The in vitro study of antibacterial effectiveness of Rosella (Hibiscus sabdariffa L.) sheath ethanol extract and water extract on Streptococcus pneumoniae was conducted by diffusion and dilution method. Basic solution amounting to 70g/100 ml of the extract was diluted into 10%, 30%, 50% and 70% for diffusion test with positive control ampicillin 10 IU, and 0,1%, 0,25%, 0,5%, 1%, and 2% ethanol extract for dilution test on S. pneumoniae. The results showed that the ethanol extract and water extract could delay of bacterium growth. Agar diffusion test (disk diffusion) was observed by diameter of bar region around the disk. At concentration 70 % among extract ethanol and water extract made bar zone wide the best, the diameter mean was estimated 25.6 mm for ethanol extract, and 24.3 mm for water extract on S. pneumoniae. In dilution test, the result showed Minimum Inhibitory Concentration (MIC) of the extract was 1% on S. pneumoniae. The result of phytochemicals test is known that ethanol extract and water extract of rosella contains of saponin, tanin, and flavonoid.